Hydrolysis of homocysteine thiolactone results in the formation of Protein‐Cys‐S‐S‐homocysteinylation. Issue 8 (15th April 2019) - Silla, Yumnam; Varshney, Swati; Ray, Arjun; Basak, Trayambak; Zinellu, Angelo; Sabareesh, Varatharajan; Carru, Ciriaco; Sengupta, Shantanu
Abstract: An increased level of homocysteine, a reactive thiol amino acid, is associated with several complex disorders and is an independent risk factor for cardiovascular disease. A majority (>80%) of circulating homocysteine is protein bound. Homocysteine exclusively binds to protein cysteine residues via thiol disulfide exchange reaction, the mechanism of which has been reported. In contrast, homocysteine thiolactone, the cyclic thioester of homocysteine, is believed to exclusively bind to the primary amine group of lysine residue leading to N‐homocysteinylation of proteins and hence studies on binding of homocysteine thiolactone to proteins thus far have only focused on N‐homocysteinylation. Although it is known that homocysteine thiolactone can hydrolyze to homocysteine at physiological pH, surprisingly the extent of S‐homocysteinylation during the exposure of homocysteine thiolactone with proteins has never been looked into. In this study, we clearly show that the hydrolysis of homocysteine thiolactone is pH dependent, and at physiological pH, 1 mM homocysteine thiolactone is hydrolysed to 0.71 mM homocysteine within 24 h. Using albumin, we also show that incubation of HTL with albumin leads to a greater proportion of S‐homocysteinylation (0.41 mol/mol of albumin) than N‐homocysteinylation (0.14 mol/mol of albumin). S‐homocysteinylation at Cys 34 of HSA on treatment with homocysteine thiolactone was confirmed using LC‐MS. Further, contrary to earlier reports, our results indicate that there is no cross talk between the cysteine attached to Cys 34 of albumin and homocysteine attached to lysine residues.